2019
DOI: 10.29333/iji.2019.1243a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Test Instrument to Assess Foreign Student’s Competence of Indonesian Language through Objective Test

Abstract: Evaluation on the foreign student's competence of Indonesian language is required to assess their achievement. This research aimed to identify the difficulty level of test instrument, analyze the difference of foreign students' competence for Indonesian language and to analyze the correlation of students' competence over various objective test formats. This research was carried out between August 2017 to August 2018 to the 16 students of Muhammadiyah Universities involved in the Darmasiswa scholarship and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The test is a necessary process to measure learning achievement (Rahmawati et al, 2019). TOEFL is a standardized test widely used across more than one hundred countries since its initial establishment in the early 1960s.…”
Section: Toefl Structure and Written Expressionmentioning
confidence: 99%
“…The test is a necessary process to measure learning achievement (Rahmawati et al, 2019). TOEFL is a standardized test widely used across more than one hundred countries since its initial establishment in the early 1960s.…”
Section: Toefl Structure and Written Expressionmentioning
confidence: 99%
“…This study showed that the lecturers responded with "rather agree" to the statement on the instrumentation variable's item. This indicates that the lecturers may have difficulty designing the instrument for their assessment practice, especially rubrics not used by the teacher (Rahmawati et al, 2019). This may be related to the instrument requirement, which must cover validity and reliability (Bariah, 2019).…”
Section: Assessment Practice On Assessing Attitude Knowledge and Skillsmentioning
confidence: 99%
“…Differences in the level of language skills of BIPA learners will have an implication on the selection of teaching materials, methods, evaluations, and other learning tools. This proves that it is crucial to carry out a placement test before a learning process begins, because foreign students need an instrument to measure their own Indonesianlanguage proficiency (Kusmiatun, 2019;Rahmawati et al, 2019a). The result of the placement test will provide teachers with information to create lesson plans and assessments that meet learners' needs (Umam, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia, on the other hand, has developed the UKBI tests for foreign-language speakers. The prototype of this test consisted of reading and comprehension tests that were developed by the Language Development and Fostering Agency based on the competency standards for BIPA graduates (Oktriono, 2019;Prasetiyo, 2019); Rahmawati, 2019a). The four prototypes of the test are not intended to be used as BIPA placement tests.…”
Section: Introductionmentioning
confidence: 99%